Tolerable upper intake level of iron damages the intestine and alters the intestinal flora in weaned piglets. Issue 9 (25th June 2020) - Ding, Haoxuan; Yu, Xiaonan; Chen, Lingjun; Han, Jianan; Zhao, Yang; Feng, Jie
Abstract : Iron is an indispensable element for animal growth but become toxic at high concentrations, while tolerable upper intake level of iron shows adverse effect in the intestine. Abstract : Iron supplementation has been an intervention to improve iron storage and prevent iron deficiency anemia in weaned piglets and the recommended nutrient intake (RNI) and tolerable upper intake levels (UL) of iron have been established. The purpose of this study is to investigate the potential harm of UL iron to the gut and microbes of weaned piglets. Thirty 23 day old weaned piglets were assigned to three dietary treatments: a basal diet supplemented with 100 (RNI), 300, and 3000 (UL) mg FeSO4 per kg diet for 28 days. Then, we used the intestinal porcine epithelial cell line (IPEC-1) as a cell model to study the effect of UL iron on the gut of weaned piglets. Weaned piglets showed a significant decrease in villus height after feeding on a UL iron diet ( P < 0.05). The protein levels of DMT1 and Zip14 decreased, and the protein levels of ferritin increased in the duodenal mucosa ( P < 0.05) of UL iron fed weaned piglets. Moreover, UL iron also increased the content of ROS and malondialdehyde and decreased the activity of superoxide dismutase in the duodenal mucosa of weaned piglets ( P < 0.05). The addition of UL iron to the diet significantly reduced the expression of tight junction proteins Claudin-1, Occludin, and ZO-1 in the duodenal mucosa of weaned piglets ( P < 0.05). In the IPEC-1 cell model, iron induced the production of cytosolic and mitochondrial ROS and reduced the mitochondrial membrane potential, which in turn led to cellular vacuolation and fibrosis. Furthermore, UL iron significantly altered the cecum flora of weaned piglets, and the relative abundance of Clostridiales, Faecalibacterium, and Prevotellaceae decreased significantly ( P < 0.05), while the relative abundance of Desulfovibrio and Anaerovibrio increased significantly ( P < 0.05). In conclusion, UL iron caused damage to the intestinal villi, induced oxidative stress, reduced iron absorption protein, damaged the intestinal barrier, and modified the intestinal microbial structure in weaned piglets.